Exponential stabilization by delay feedback control for highly nonlinear hybrid stochastic functional differential equations with infinite delay. (May 2021) - Mei, Chunhui; Fei, Chen; Fei, Weiyin; Mao, Xuerong
Abstract: Given an unstable hybrid stochastic functional differential equation, how to design a delay feedback controller to make it stable? Some results have been obtained for hybrid systems with finite delay. However, the state of many stochastic differential equations are related to the whole history of the system, so it is necessary to discuss the feedback control of stochastic functional differential equations with infinite delay. On the other hand, in many practical stochastic models, the coefficients of these systems do not satisfy the linear growth condition, but are highly nonlinear. In this paper, the delay feedback controls are designed for a class of infinite delay stochastic systems with highly nonlinear and the influence of switching state.